Virtually home: Exploring the potential of virtual reality to support patient discharge after stroke. (February 2017) - Threapleton, Kate; Newberry, Karen; Sutton, Greg; Worthington, Esme; Drummond, Avril
Introduction: The level of assessment and intervention received by patients prior to discharge varies widely across stroke services in the United Kingdom. This study aimed to explore the potential value of virtual reality in preparing patients for discharge following stroke. Method: Semi-structured interviews were carried out with 13 occupational therapists, eight patients with a stroke and four community stroke survivors. Views were sought of the perceived acceptability, potential utility and limitations of a 'virtual home' environment for use in pre-discharge education and assessment. Data were analysed thematically. Findings: Interviewees found the virtual home to be an acceptable and visual means of facilitating discussions about discharge. It was perceived as valuable in assessing patient insight into safety risks and exploring the implications of installing assistive equipment at home. Limitations were identified relating to specific software issues and the use of virtual reality with patients with cognitive or perceptual impairments. Conclusion: The results demonstrate the potential utility of the virtual home within stroke rehabilitation. Patients and therapists engaged with the virtual home and, moreover, made practical suggestions for future development. Feasibility and pilot testing in a clinical setting is required to compare the use of the virtual home with traditional approaches of pre-discharge assessment.